New 3D fault model for eastern Flanders (Belgium) providing insights on the major deformation phases in the region since the late Paleozoic. (January 2023) - Deckers, J.; Rombaut, B.; Broothaers, M.; Dirix, K.; Debacker, T.
Abstract: A new 3D fault model was created for the Upper Paleozoic to Cenozoic subsurface in eastern Flanders (Belgium). The model was based on the integration of 2D seismic interpretations, borehole and gravimetric data, as well as coal mining and topographic maps. Four major tectonic phases, taking place during the latest Paleozoic, Jurassic, Late Cretaceous and Cenozoic, shaped the fault network. The latest Paleozoic phase was transpressional and expressed by local folding of the Carboniferous strata underneath the base Permian unconformity. The largest anticlines were asymmetric, with amplitudes of up to 500 m and SSW-NNE oriented axal planes. The subsequent Jurassic phase caused normal faulting across the area, resulting in the development of the northeast-dipping, western border fault systems of the Campine Basin and Roer Valley Graben. Fault strikes were predominantly WNW-ESE to NNW-SSE. Both fault directions were most likely inherited from early Carboniferous and older tectonic phases. Jurassic fault reactivation explains the activity along fault populations with different orientations as well as the linkage of these faults into long (>10 km) systems, despite displaying generally relatively small vertical throws (<500 m). Soft-linked boundaries (accommodation zones) between Jurassic fault domains are located on top of the largest latest Paleozoic transpressional anticlines. The Late Cretaceous major tectonic phase was compressional and involved inversion of the Roer Valley Graben with subsequent subsidence and carbonate deposition in the flanking Campine Block. During the Cenozoic extensional phase, most normal faults that developed were rooted in Jurassic faults and therefore displayed similar WNW-ESE to NNW-SSE strikes. Cenozoic extension was, however, weaker than Jurassic extension; Cenozoic fault numbers, lengths and vertical throws were smaller than during the Jurassic phase. Also during the Cenozoic phase, faulting was more localized onto the pre-existing Roer Valley Graben border fault system compared to the more diffuse Jurassic faulting. The Cenozoic faults were generally planar, whereas some of its Jurassic roots near and in the border fault system of the Roer Valley Graben were listric.